Oral Outbreak of Chagas Disease in Santa Catarina, Brazil: Experimental Evaluation of a Patient’s Strain - Domingues, Carolina S. (PLoS One, 2015)
Chagas disease is a worldwide public health problem. Although the vectorial transmission of Chagas disease has been controlled in Brazil there are other ways of transmission, such as the ingestion of T. cruzi contaminated food, which ensures the continuation of this zoonosis. Here, we demonstrate the influence of the inoculation route on the establishment and development of the SC2005 T. cruzi strain infection in mice. Groups of Swiss mice were infected intragastrically (IG) or intraperitoneally (IP) with the T. cruzi SC2005 strain derived from an outbreak of oral Chagas disease. The results revealed that 100% of IP infected mice showed parasitemia, while just 36% of IG infected showed the presence of the parasite in blood. The parasitemia peaks were later and less intense in the IG infected mice. Mortality of the IP infected animals was more intense and earlier when compared to the IG infected mice. In the IP infected mice leucopenia occurred in the early infection followed by leucocytosis, correlating positively with the increase of the parasites. However, in the IG infected mice only an increase in monocytes was observed, which was positively correlated with the increase of the parasites. Histopathological analyses revealed a myotropic pattern of the SC2005 strain with the presence of inflammatory infiltrates and parasites in different organs of the animals infected by both routes as well as fibrosis foci and collagen redistribution. The flow cytometric analysis demonstrated a fluctuation of the T lymphocyte population in the blood, spleen and mesenteric lymph nodes of the infected animals. T. cruzi DNA associated with the presence of inflammatory infiltrates was detected by PCR in the esophagus, stomach and intestine of all infected mice. These findings are important for the understanding of the pathogenesis of T. cruzi infection by both inoculation routes.